Uma avaliação do impacto do trabalho remoto no desenvolvimento de software por meio do SCRUM - Maffei, Debora Cristina (Universidade Federal de São Carlos, 2021)
Agile Methodologies, especially SCRUM, emerged as an alternative to traditional methodologies, such as the Cascade Model. Agile approaches are configured as alternatives so that companies do not demand too much time with documentation, bureaucracy and excessive planning. In SCRUM, planning is carried out on a smaller time scale, providing the customer with time increments in certain periods that facilitate the necessary modifications during the project, and not identified at the end. With the beginning of the COVID-19 pandemic, caused by the new corona virus SARS-CoV-2, and the need for social distance, society as a whole has been adapting to reduce the contamination by the virus. Several companies are adopting the remote work regime, as a way to continue their activities and also to avoid the contamination of their employees. This research aimed to understand the impact of remote work on software development through SCRUM. Therefore, a qualitative research approach was used through a single case study. Interviews were conducted with the main members of the SCRUM team of a software development company in the interior of São Paulo. We tried to record the experience of professionals who use the framework in a home office regime. Topics directly related to SCRUM and work, mental and physical health, family relationships, infrastructure and comfort were addressed. This work brings evidence that the use of the SCRUM agile methodology is totally viable and recommended for companies that are working in remote systems
An assessment of the impact of home office on software development through SCRUM
Keywords: Metodologia ágil; Desenvolvimento de software; Pandemia; Trabalho Remoto; Covid-19; Home Office; SCRUM; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO